2023
DOI: 10.1038/s41467-023-38196-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of lung adenocarcinoma in East Asia and comparison with a European population

Abstract: Lung adenocarcinoma is the most common type of lung cancer. Known risk variants explain only a small fraction of lung adenocarcinoma heritability. Here, we conducted a two-stage genome-wide association study of lung adenocarcinoma of East Asian ancestry (21,658 cases and 150,676 controls; 54.5% never-smokers) and identified 12 novel susceptibility variants, bringing the total number to 28 at 25 independent loci. Transcriptome-wide association analyses together with colocalization studies using a Taiwanese lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 91 publications
(154 reference statements)
2
12
0
Order By: Relevance
“…Environmental tobacco smoke contains genotoxic and carcinogenic byproducts of cigarette smoke, which are the main cause of lung adenocarcinoma (LUAD), the most common histologic subtype among never-smokers . In addition to environmental carcinogens, several authors of the present study recently conducted the largest multi-ancestry genome-wide association study (GWAS) of lung cancer among East Asian and European populations and identified 25 single nucleotide variants (SNVs) associated with LUAD among East Asian individuals, which highlights the importance of genetic susceptibility to the etiology of LUAD …”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Environmental tobacco smoke contains genotoxic and carcinogenic byproducts of cigarette smoke, which are the main cause of lung adenocarcinoma (LUAD), the most common histologic subtype among never-smokers . In addition to environmental carcinogens, several authors of the present study recently conducted the largest multi-ancestry genome-wide association study (GWAS) of lung cancer among East Asian and European populations and identified 25 single nucleotide variants (SNVs) associated with LUAD among East Asian individuals, which highlights the importance of genetic susceptibility to the etiology of LUAD …”
Section: Introductionmentioning
confidence: 81%
“…Data analysis was conducted from January 17 to July 15, 2022. We derived a polygenic risk score (PRS) using 25 independent SNVs that have previously reached genome-wide significance (ie, P = 5 × 10 −8 ) in a recently conducted 2-stage GWAS with 21 658 cases of histologically confirmed LUAD in East Asian populations from Taiwan, Mainland China, Japan, Singapore, and Korea . The PRS was calculated for each individual (i) as the following linear combination:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…77 Genomewide association studies have identified rare-variant associations, some of which vary in prevalence by race. 78,79 A history of lung disease is associated with an increased risk of lung cancer. 80,81 Diseases that increase risk include asthma and pneumonia among those who have never smoked; emphysema among those with a history of smoking; and pulmonary fibrosis, including asbestosis, chronic bronchitis, chronic obstructive pulmonary disease, and tuberculosis, regardless of smoking status.…”
Section: Risk Factors Other Than Tobacco Usementioning
confidence: 99%
“…The first is genome‐wide association study (GWAS), which is applied to explore the genetic predisposition of common genetic variants for cancer. Up to now, over 50 susceptibility single nucleotide polymorphisms (SNPs) have been identified to be associated with lung cancer risk in Chinese and European populations [ 5 , 6 , 7 , 8 , 9 ]. The second is to identify pathogenic/likely pathogenic (P/LP) germline variants in cancer susceptibility genes, making it possible to explore the functional impact of rare and very rare germline variants in the cancer development [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%